دور استراتيجية البرامج التدريبية على أداء العاملين بوزارة اإلعالم العمانية في ضوء خطة التنمية المهنية - Asma Abd Rahman; Busaidy Al-Suhad Said Humaid (Journal Of Humanities, Language, Culture And Business, 2024)
Non-Indexed Publication